The school as an arena for mental health work: exploring the perspectives of frontline professionals on mental health work in Norwegian schools - Berg, Anita; Appoh, Lily; Ørjasæter, Kristin B. (Frontiers in Public Health, 2024)
Introduction Children and adolescents are increasingly facing mental health problems. Schools play a crucial role in promoting mental health, as they provide a unique setting where children interact with adults outside their homes. Methods This paper explores mental health work in Norwegian schools from the perspective of frontline professionals namely, class teachers, social workers, and public health nurses. We conducted four focus group interviews involving 22 of these professionals from nine primary and secondary schools. Results The school professionals view mental health work as an integral part of the school's mission and associate their work with promoting mental wellbeing, strengthening self-esteem, and building resilience among pupils. The professionals noted an expansion in their roles and an increase in expectations to undertake mental health work, even though it is not formally part of their job descriptions. Additionally, they play varied and complementary roles in supporting the pupils' mental health daily. As school professionals, they strive to balance universal health promotion with providing individualized mental health care. Discussion These results call for coordinated efforts and interdisciplinary collaboration within the school and discussion regarding the school's role in mental health care for children and adolescents.